Penerapan Layanan Bimbingan Kelompok dengan Teknik Reinforcement untuk Meningkatkan Self-esteem Pada Body image Mahasiswi FKIP Universitas PGRI Banyuwangi (International Forum of Researchers and Lecturers, 2025)
Issues related to self-esteem and body image have become a significant psychological challenge among female students, particularly at the Faculty of Education and Educational Sciences of PGRI University Banyuwangi. Factors such as social pressure, unrealistic beauty standards, and low self-acceptance lead to many female students experiencing a lack of confidence in their physical appearance. Therefore, appropriate psychological intervention is needed to help them develop a more positive mindset. positive mindset. This study employs a quantitative approach with a one-group pretest-posttest design. The research subjects are female students at the Faculty of Education and Teacher Training (FKIP) of PGRI University Banyuwangi who have low self-esteem regarding their body image. The intervention is conducted through group counseling services using reinforcement techniques and supported by modeling techniques. The results of the study showed a significant increase in self-esteem regarding body image among female students after participating in the group counseling service. The application of reinforcement techniques proved effective in strengthening positive behaviors and mindsets regarding body image. Thus, this service can be used as a counseling strategy to improve the psychological and social self-confidence of female students.